Double diffusive effect on geometrical characteristics of inclined thermal-saline negatively buoyant jets. (1st August 2022) - Ardalan, Hossein; Vafaei, Fereidon; Amiri, Leila; Goharikamel, Davood; Azizi, Mohammad
Abstract: In this paper the turbulent reversible thermal-saline buoyant jets discharged upwards at angles 30 0, 45 0 and 60 0, into a stagnant ambient are experimentally studied. In all cases, the flow finally behaves as a negatively buoyant jet, even in cases where the flow has positive buoyancy at the source. In reversible thermal-saline jets, there is a nonlinear relationship of the geometric characteristics of negatively thermal-saline buoyant jets with the relative density. The highest values of centerline peak and terminal rise height of jets were observed in the discharge angle of 60 0, and the lowest values were observed in the discharge angle of 30 0 . Also, the value of horizontal distance to the centerline peak and return point for the discharge angle of 30 0 shows a higher value than the angle of 45 0 and 60 0 . Graphical abstract: Image 1 Highlights: The dispersion mechanism for the reversible thermal-saline jets is different from the conventional dense jets. The relationship of the geometric characteristics of reversible thermal-saline jets with the relative density is nonlinear. The geometric characteristics of the reversible thermal-saline jets are a function of the densimetric Froude number, relative density and discharge angle.